2001
DOI: 10.1084/jem.193.12.1425
|View full text |Cite
|
Sign up to set email alerts
|

A Transcription Function for the T Cell–Specific Adapter (Tsad) Protein in T Cells

Abstract: T cell–specific adapter (TSAd) protein is an Src homology 2 (SH2) domain–containing adapter molecule implicated in T cell receptor for antigen (TCR)-mediated interleukin 2 (IL-2) secretion in T cells. Here, we demonstrate that a substantial fraction of TSAd is found in the T cell nucleus. Nuclear import of TSAd is an active process that depends on TSAd SH2 domain recognition of a phosphotyrosine-containing ligand. Importantly, we show that TSAd can act as a potent transcriptional activator in T cells. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 17 publications
(18 reference statements)
2
67
0
1
Order By: Relevance
“…Recently the adapter protein ALX or HSH2 was found to have substantial homology to TSAd [30]. Both ALX and TSAd were found to inhibit the activity of IL-2 promoter constructs [9,30]; however, TSAd has also been found to promote IL-2 promoter activity [10], and activated T cells from TSAd knockout mice express less IL-2 [6]. These apparently conflicting results [11] may be explained in several ways.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recently the adapter protein ALX or HSH2 was found to have substantial homology to TSAd [30]. Both ALX and TSAd were found to inhibit the activity of IL-2 promoter constructs [9,30]; however, TSAd has also been found to promote IL-2 promoter activity [10], and activated T cells from TSAd knockout mice express less IL-2 [6]. These apparently conflicting results [11] may be explained in several ways.…”
Section: Discussionmentioning
confidence: 83%
“…We previously showed that TSAd inhibits proximal signaling events in Jurkat T cells stably expressing TSAd, possibly by interfering with Lck activity [9]. Others have shown that TSAd is translocated to the nucleus in activated Jurkat T cells, and proposed that TSAd could function as a transcription adapter protein positively influencing IL-2 promoter activity [10]. T cells from mice lacking TSAd expression show reduced production of IL-2 and IFN-c [6], and these mice develop a spontaneous systemic autoimmune disease as they grow older [11].…”
Section: Introductionmentioning
confidence: 99%
“…2 There are also indications that TSAd may be involved in transcriptional regulation in the cell nucleus. 3 Recently, it was reported that mice lacking the SH2D2A gene develop spontaneous systemic lupus-like autoimmune disease when they get older, probably due to a defect in activation-induced T-cell death. 4 The SH2D2A gene encoding TSAd contains a variable number (n ¼ 13-33) of GA repeats in its promoter region located at position À340 upstream of the first coding ATG.…”
mentioning
confidence: 99%
“…The two proteins exhibit 36% overall homology, and 57% when only the SH2 domains are compared (6). SH2 domain mutations in either RIBP or ALX abrogate function (8,9). Analysis of RIBPdeficient mice demonstrated that RIBP is a positive regulator of peripheral T cell activation.…”
mentioning
confidence: 99%